2018
DOI: 10.1002/2017tc004816
|View full text |Cite
|
Sign up to set email alerts
|

Differential Exhumation Across the Longriba Fault System: Implications for the Eastern Tibetan Plateau

Abstract: The deformation processes at work across the eastern margin of the Tibetan Plateau remain controversial. The interpretation of its tectonic history is often polarized between two deformation models: ductile flow in the lower crust and shortening and crustal thickening accommodated by brittle structures in the upper crust. Many geological investigations on this plateau margin focused on the Longmen Shan, at the western edge of the Sichuan Basin. However, the Longriba fault system (LFS) located 200 km northwest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 92 publications
(216 reference statements)
1
20
1
Order By: Relevance
“…Our SWS observations (Stations s149 to s151; Figures and b) in the Longriba fault vicinity show obvious fault‐parallel FPDs, which is comparable with the relatively high strain rates near the fault (Figure ). The Longriba fault has been an important structure and block boundary within the Songpan‐Ganzi terrane since at least 10–15 Ma (Ansberque et al, ). The fault may contribute to absorb the slip rate of the Kunlun fault and change the crustal kinematics at the eastern Tibetan margin (Gan et al, ; X.‐W.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our SWS observations (Stations s149 to s151; Figures and b) in the Longriba fault vicinity show obvious fault‐parallel FPDs, which is comparable with the relatively high strain rates near the fault (Figure ). The Longriba fault has been an important structure and block boundary within the Songpan‐Ganzi terrane since at least 10–15 Ma (Ansberque et al, ). The fault may contribute to absorb the slip rate of the Kunlun fault and change the crustal kinematics at the eastern Tibetan margin (Gan et al, ; X.‐W.…”
Section: Discussioncontrasting
confidence: 99%
“…GPS measurements (Gan et al, ) show an abrupt change in lateral extrusion velocity crossing the fault. Despite its relatively small scale, the average dextral rate of 5.6 ± 2.0 mm/year and the crustal shorting rate of 0.55 mm/year suggest that the Longriba fault is currently very active (Ansberque et al, ; X.‐W. Xu et al, ).…”
Section: Geological Settingmentioning
confidence: 99%
“…Several studies [Xu and Kamp, 2000;Wilson and Fowler, 2011;Li et al, 2012;Cook et al, 2013;Tian et al, 2013] reported thermochronological data from other parts of the Longmen Shan, which are broadly consistent with the results outlined above. Other studies from adjacent areas reported late Miocene [Clark et al, 2005;Enkelmann et al, 2006;Ouimet et al, 2010;Duvall et al, 2012;Tian et al, 2015], Oligocenemiddle Miocene [Tian et al, 2013[Tian et al, , 2014Shen et al, 2016;Zhang et al, 2016;Ansberque et al, 2018] or Paleocene to Eocene and Miocene [Liu-Zeng et al, 2018] phases of exhumation with spatially variable exhumation rates (Fig. 1b).…”
Section: Previous Thermochronological Studiesmentioning
confidence: 77%
“…Both tectonic dynamics can, however, coexist and be consistent with a southeast thrusting during the Early Cretaceous, resulting in the formation of basement‐slice‐imbricated structures (Airaghi et al, ; Xue et al, ; this study). Furthermore, a Cretaceous reactivation is also recorded ~200 km NW of the LMS, in the Longriba fault zone and in the Aba block (Ansberque et al, ; Tan et al, ), suggesting that a large portion of the eastern Tibet remained coupled during Cretaceous exhumation (Ansberque et al, ).…”
Section: Discussionmentioning
confidence: 99%